The relationship between self confidence and psychological performance on track and field student-athletes / Vincent Parnabas, Julinamary Parnabas and Antoinette Mary Parnabas - Parnabas, Vincent; Parnabas, Julinamary; Parnabas, Antoinette Mary (Universiti Teknologi MARA, 2023)
Psychological performance is a crucial ingredient for athletes' success in sport. In many research reviews, researchers have found that low level of self-confidence can have deteriorating effect on athletes' performance. However, to date there has been very limited research to examine self confidence level and psychological performance according to the levels of skills, especially on track and field athletes. The main aim of the study was to compare and correlate the self-confidence and psychological performance level among track and field athletes who represent national, state, district and university level during Sport between Universities event. Data was collected from 77 student-athletes, using Self Confidence and Psychological Performance Inventory (PPI). The results showed that national level athletes obtained the highest score on self-confidence, F (3, 77) = 15.212, and psychological sport performance F (3, 77) = 13.442. Positive correlation (r=0.007) existed between self-confidence and psychological performance. Based on the current results, it is recommended that sport psychologists, sport counsellors and coaches in Malaysia use the findings to design appropriate training programs to help athletes acquire higher level of self-confidence to enhance athletes' psychological performance in sports.